1996
DOI: 10.1007/bf00041013
|View full text |Cite
|
Sign up to set email alerts
|

EPR and ENDOR studies of the water oxidizing complex of Photosystem II

Abstract: A comparative study of X-band EPR and ENDOR of the S2 state of photosystem II membrane fragments and core complexes in the frozen state is presented. The S2 state was generated either by continuous illumination at T=200 K or by a single turn-over light flash at T=273 K yielding entirely the same S2 state EPR signals at 10 K. In membrane fragments and core complex preparations both the multiline and the g=4.1 signals were detected with comparable relative intensity. The absence of the 17 and 23 kDa proteins in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 42 publications
2
61
0
Order By: Relevance
“…Probably, they function as ligands to the Mn and Ca ions or form a hydrogen bond network around the Mn cluster to participate in the reaction mechanism of water oxidation. This view is consistent with the previous ESEEM and ENDOR results, which showed the presence of several exchangeable protons in the vicinity of the Mn cluster in the S 0 , S 1 , and S 2 states (12)(13)(14)(15). Also, this is consistent with the recent structural models of the WOC and the mechanism of water oxidation proposed by quantum chemical calculations (39-41) based on the X-ray crystal structures and the EXAFS data (5)(6)(7).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Probably, they function as ligands to the Mn and Ca ions or form a hydrogen bond network around the Mn cluster to participate in the reaction mechanism of water oxidation. This view is consistent with the previous ESEEM and ENDOR results, which showed the presence of several exchangeable protons in the vicinity of the Mn cluster in the S 0 , S 1 , and S 2 states (12)(13)(14)(15). Also, this is consistent with the recent structural models of the WOC and the mechanism of water oxidation proposed by quantum chemical calculations (39-41) based on the X-ray crystal structures and the EXAFS data (5)(6)(7).…”
Section: Resultssupporting
confidence: 92%
“…Mass spectrometric measurements have shown that the rate of 18 O incorporation has biphasic kinetics throughout the S states, representing two distinct substrate molecules with fast and slow exchange rates (10,11). Several exchangeable protons, including those from substrate water, have been detected in the vicinity of the Mn cluster in the S 0 , S 1 , and S 2 states using the ENDOR and ESEEM techniques (12)(13)(14)(15)(16). Also, a water-exchangeable oxygen strongly coupled to the Mn cluster in the S 2 state was recently detected by 17 O-HYSCOPE spectroscopy (17).…”
mentioning
confidence: 98%
“…As described earlier, 14,24,75 the magnetic dipole tensor component of a bridging ligand consists of contributions from the hyperfine coupling of the ligand to each metal site, with the contribution of each weighted by the spin projection coefficient for each metal site. 14,24,75 The unique axis for the site hyperfine for each oxygen bridge should lie along the Mn-O bond.…”
Section: Acs Paragon Plus Environmentmentioning
confidence: 99%
“…14,24,75 The unique axis for the site hyperfine for each oxygen bridge should lie along the Mn-O bond. Assuming a ≈90° Mn-OMn bond, summing the two site hyperfine tensors yields a projected 17 O hyperfine tensor that has approximately rhombic symmetry (η = 0.6).…”
Section: Acs Paragon Plus Environmentmentioning
confidence: 99%
“…Direct structural information is lacking (vide supra), and even the number of water molecules around the cluster is not known. Indirect lines of evidence for binding of water molecules to Mn 4 O X Ca were gathered from electron-nuclear double resonance (ENDOR) (Fiege et al 1996;Yamada et al 2007) and electron-spin echo envelope modulation (ESEEM) studies (Gregor et al 2005;Å hrling et al 2006). FTIR measurements revealed the existence of water molecule(s) with asymmetric hydrogen bonding of the two protons in the S 1 state.…”
Section: Coordination Sphere Of the Mn 4 O X Ca Clustermentioning
confidence: 99%